ISLAMIC FINTECH AND FINANCIAL INCLUSION IN EMERGING MARKETS: QUALITATIVE EVIDENCE FROM INDONESIA - Ranto Rinda Trihariyanto; M Saifu Rizal; Oktami Achni; Darul Qotni Abbas (Jurnal Dinamika Ekonomi Syariah, 2026)
This study examines the development of Islamic Financial Technology (fintech) and its role in promoting financial inclusion in Indonesia. The rapid advancement of technology has significantly influenced the financial sector, leading to the emergence of Islamic fintech, which integrates financial technology with Sharia principles that prohibit interest (riba), gambling (maisir), and uncertainty (gharar). Using a qualitative approach, this research employs literature review, documentation, and analysis of reports from relevant institutions and regulatory frameworks. The findings indicate that Islamic fintech has experienced substantial growth in recent years, reflected in the increasing number of platforms, product diversification, and the adoption of Sharia-compliant digital technologies. Furthermore, Islamic fintech contributes significantly to expanding financial access, particularly for unbanked and underbanked populations, by providing services that are more accessible, efficient, and aligned with Islamic values